Advancing Calf Care: The Development and Standardization of Knowledge Test for Calf Management and Feeding Practices - , Niharika Thakur; , Rajesh Kasrija; , Parminder Singh (Archives of Current Research International, 2025)
Dairy farmers often lack proficiency in calf management and feeding practices, critical aspects of effective animal husbandry. This gap can result in substantial production and reproduction losses in the near future. To mitigate these issues, the development and standardisation of the knowledge test was done to evaluate stakeholders' understanding of calf management and feeding practices. 74 items focusing on essential aspects of calf management and feeding practices were compiled as multiple-choice or open-ended questions. These were presented to 36 dairy farmers who own calves to solicit their responses and were specifically chosen for assessing test reliability and validity. The analysis of data was done for difficulty and discrimination index and only 32 items fulfilled the criteria of difficulty index 30-90 and discrimination index ranging from 0.1-0.8 were selected for further analysis of reliability and validity. The split-half reliability was determined using the Spearman-Brown prophecy formula, demonstrating a robust score of 0.91, indicating strong internal consistency. Furthermore, Cronbach’s Alpha coefficient was computed at 0.88, affirming high reliability across the selected items. Item validity was determined with the help of Aiken’s V coefficient, with all items displaying coefficients ≤ 0.80 (P<0.05), reinforcing the test's validity. Accordingly, the final knowledge test comprising 32 items on calf management and feeding practices was standardized. The test serves to assess stakeholders' knowledge gaps in calf management and feeding practices, facilitating targeted interventions to enhance their knowledge. This transformation of knowledge into productivity can optimize outcomes effectively. It can be said that the items involved in the test are straightforward and easy to understand, making the test practical and user-friendly.